KONTRIBUSI PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH (PAD) DKI JAKARTA DI TAHUN 2020 SAMPAI DENGAN 2022 BERDASARKAN PERDA NOMOR 12 TAHUN 2011: Contribution Of Advertisement Tax To Regional Regional Income (Pad) Of Dki Jakarta In 2020 To 2022 Based On Regional Regulation Number 12 Of 2011 - Lamsihar Raymond Davidson; Januardo Sihombing (Faculty of Law, Universitas Trisakti, 2025)
Difficulties in determining the accurate selling value of advertisement tax objects often lead to differences in perception between taxpayers and tax officers; a lack of taxpayer awareness to pay advertisement taxes; insufficient supervision and law enforcement against tax violations, which result in many illegal advertisements appearing in public spaces; and a complex and bureaucratic advertisement tax administration system, making it difficult for taxpayers to fulfill their obligations. This study uses a normative and descriptive approach to analyze the management of advertisement tax in DKI Jakarta. This study identifies problems concerning difficulties in determining the value of advertisement tax objects, low taxpayer awareness, weak supervision, and administrative complexity affecting tax compliance. Data were collected from legislation and legal literature to provide an in-depth understanding of the applicable legal framework. The findings indicate that although local regulations provide a clear legal framework, challenges remain, such as difficulties in identifying digital advertisement tax objects and differences in rates compared to other regions. Technical constraints in supervising violations, as well as the need to enhance the capacity of officers and inter-agency coordination, are key areas for improvement. With the results of the research and conclusion, it was found that the management of advertisement tax requires systematic improvements to increase taxpayer compliance and the effectiveness of supervision.